2023
DOI: 10.1289/ehp11506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollution on Heart Failure: Systematic Review and Meta-Analysis

Abstract: Background: Heart failure (HF) poses a significant global disease burden. The current evidence on the impact of air pollution on HF remains inconsistent. Objectives: We aimed to conduct a systematic review of the literature and meta-analysis to provide a more comprehensive and multiperspective assessment of the associations between short- and long-term air pollution exposure and HF from epidemiological evidences. Methods: Three databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Some cardiovascular conditions (i.e., ischemic heart disease, pulmonary circulation impairment, heart conduction disorders, heart failure) were also associated with a greater vulnerability to NO 2 [ 29 ]. A recent meta-analysis reported an increased risk of death from heart failure associated with short-term exposure to PM and NO 2 as well as sulphur dioxide and carbon monoxide, but not O 3 [ 30 ]. Our investigation also suggested a higher vulnerability to O 3 in people with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Some cardiovascular conditions (i.e., ischemic heart disease, pulmonary circulation impairment, heart conduction disorders, heart failure) were also associated with a greater vulnerability to NO 2 [ 29 ]. A recent meta-analysis reported an increased risk of death from heart failure associated with short-term exposure to PM and NO 2 as well as sulphur dioxide and carbon monoxide, but not O 3 [ 30 ]. Our investigation also suggested a higher vulnerability to O 3 in people with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study conducted using United Kingdom Biobank data demonstrated a 31% increase in HF incidence due to long-term exposure to air pollutants, after adjustment for confounding variables [36]. Some previous data have shown that PM2.5, PM10, and NO 2 represent the main pollutants associated with the risk of developing HF and that this relationship may be influenced by genetic polymorphisms and susceptibility [36,37].…”
Section: Heart Failurementioning
confidence: 99%
“…24 For example, cohort studies in China and Canada show that chronic PM 2.5 exposure is significantly associated with HF. 25,26 However, another study in South Korea comes to the opposite conclusion that HF is negatively associated with PM 2.5 . 27 Current evidence mainly focuses on the combined effects of global PM 2.5 on CVDs, and limited reports mention the importance of PM 2.5 -loaded components in this process, 16 especially organic components.…”
Section: Introductionmentioning
confidence: 98%